2012
DOI: 10.1179/1351000212y.0000000023
|View full text |Cite
|
Sign up to set email alerts
|

A single exposure of rats to water-immersion restraint stress induces oxidative stress more severely in the thymus than in the spleen

Abstract: It is indicated that a single expose of rats to WIRS induces oxidative stress more severely in the thymus than in the spleen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Clearly, it is difficult to tease apart the differential modulation and generation of the CD8 + CD122 + T cell response during pregnancy, as CD8 + CD122 + T cell frequencies remained low upon supplemental progesterone and associated placental Hmox1 upregulation in stress-challenged dams. This observation suggests that Hmox1-independent mechanisms, such as direct effects on maternal thymus (73,74), low levels of TGF-β (75), or selective glucocorticoid-induced CD8 + Treg apoptosis in response to stress, could account for the impaired generation of this cell subset.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, it is difficult to tease apart the differential modulation and generation of the CD8 + CD122 + T cell response during pregnancy, as CD8 + CD122 + T cell frequencies remained low upon supplemental progesterone and associated placental Hmox1 upregulation in stress-challenged dams. This observation suggests that Hmox1-independent mechanisms, such as direct effects on maternal thymus (73,74), low levels of TGF-β (75), or selective glucocorticoid-induced CD8 + Treg apoptosis in response to stress, could account for the impaired generation of this cell subset.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma epinephrine and norepinephrine levels were increased via the activation of the plasma enzymes in fasted rats under 6 h of WIRS ( Arakawa et al., 1997 ). Ohta et al demonstrated that WIRS exposure of rats induced severe oxidative stress in immune organs ( Ohta et al., 2012 ). However, the pathogenesis of intestinal mucosal injury induced by water restraint stress remains unclear.…”
Section: Introductionmentioning
confidence: 99%